FORMATION OF PROFESSIONAL COMPETENCE IN PHILOLOGY STUDENTS - Lagai Yelena Alexandrovna (American Journals Publishing, 2023)
The article emphasizes the need to develop professional communicative competence among philology students, which helps future specialists to successfully solve communicative tasks of a professional nature. The expediency of systematic work based on a set of exercises is substantiated.
Keywords: Professional competence; philology students; functional style; scientific style; exercise system.